Serum Cystatin C in the Diagnosis of Early DN and Its Comparison with UACR: A Cross-sectional Observational Study - Praveen K Malik; Abhishek; Deepali Kaushik; Anjali (Bengal Physician Journal)
Introduction: In India, diabetic nephropathy (DN) constitutes approximately 46% of chronic renal diseases in the elderly population, becoming the primary cause of end-stage renal disease (ESRD). Early detection of DN enables timely intervention and prevents progression to ESRD. Aim of study: To study serum cystatin C as a biomarker of early DN in comparison with urinary albumin-to-creatinine ratio (UACR). Materials and methods: This cross-sectional observational study was conducted in the Department of General Medicine of Employees’ State Insurance Corporation Medical College and Hospital, Faridabad, from 2021 to 2024 after obtaining clearance from our institutional ethical committee. The duration for the sample collection was 1 year. A total of 50 consenting diabetic patients who fulfilled the inclusion and exclusion criteria within the study period were included in the study. In diabetic patients with a glomerular filtration rate (GFR) of ≥30 mL/min/1.73 m2, indicating early DN (stages I, II, and III according to Mogensen’s classification), serum cystatin C and UACR were assessed. We conducted a comparative analysis of serum cystatin C and the UACR as biomarkers for early DN. Results: Among 50 patients, 68% of the patients were aged between 41 and 50 years. The mean age was 43.06 ± 6.9 years. Among total subjects, 52% were males and 48% were females. The most common complaints were polyuria (56%), fatigue (56%), polydipsia (38%), and weight loss (34%). Mean values of diabetic parameters for fasting blood sugar (FBS), postprandial blood sugar (PBS), random blood sugar, and HbA1c were 224.82 ± 79.02 mg/dL, 341 ± 90.1 mg/dL, 331.56 ± 76.98 mg/dL, and 9.85 ± 2.37%, respectively. Mean duration of diabetes was 4.4 ± 3.48 years. About 30% of the cases were classified as stage I, 22% as stage II, and 48% as stage III. Serum cystatin C levels were elevated in 78% of cases. The mean serum cystatin C levels was 1.19 ± 0.39 mg/L, UACR was 95.22 ± 102.15 mg/gm, and GFR was 102.62 ± 28.54 mL/min/1.73 m². Serum cystatin C levels showed a significant positive correlation with UACR with an r-value of 0.530 and significant p-value of < 0.001. Conclusion: This study suggests that serum cystatin C is a valuable biomarker for early detection of DN and its rise before the onset of microalbuminuria highlights its utility in clinical practice.